Zoonosis screening in Spanish immunocompromised children and their pets - Garcia-Sanchez, Paula; Romero-Trancón, David; Falces-Romero, Iker; Navarro Carrera, Paula; Ruiz-Carrascoso, Guillermo; Carmena, David; Casares Jiménez, María; Rivero-Juárez, Antonio; Moya, Laura; Rodón, Jaume; Esperón, Fernando; Pérez-Hernando, Belén; et al. (Frontiers in Veterinary Science, 2024)
Introduction: Although pets provide several social-emotional benefits for children, the risk of zoonosis must be considered among immunocompromised individuals.Methods: A prospective study was conducted in a tertiary hospital including immunocompromised patients younger than 20 years owning dogs and/or cats.Colonization and/or infection was evaluated by stool studies, bacterial swabs, blood polymerase chain reaction and serological studies in both patients and their pets, to evaluate potential zoonotic transmission occurrence.We included 74 patients and their 92 pets (63 dogs, 29 cats). Up to 44.6% of the patients and 31.5% of the pets had at least 1 positive result. Up to 18.4% of pets' fecal samples were positive (bacteria, parasites or hepatitis E virus). No helminths were observed despite the high frequency of incorrect intestinal deworming practices. Among children, gastrointestinal microorganisms were found in 37.3% (primarily Clostridium difficile). Colonization by Staphylococcus pseudintermedius was common among pets (8%) but not among children (0.0%). No shared colonization between owners and pets was observed, except in one case (Blastocystis in both patient and pet feces). Among patients, serologies were positive for Strongyloides stercoralis (14.8%), Toxocara canis (3.2%), Bartonella henselae (19.1%) and hepatitis E (5.6%). Serology was positive for Rickettsia spp. (22.6%) and Babesia spp. (6.5%) in dogs and for Leishmania spp. (14.3%) and Toxoplasma spp. (14.3%) in cats.Conclusions: Exposure to zoonotic agents was detected in both patients and pets; however, shared colonization events were almost nonexistent. In our cohort, dogs and cats do not appear to entail high zoonosis transmission risk for immunocompromised patients.